The Influence of Marketing Mix Performance on Costumers’ Purchase Decision of Packaged Rendang Sold by MSMEs in Payakumbuh, West Sumatra, Indonesia - Rahmi, Elfi; Putra, Aronal Arief (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
This study aims to analyze the influence of product, price, place, promotion, and services on purchasing decisions for rendang in Payakumbuh, West Sumatra. The study was conducted on 51 Micro Small Medium Enterprises (MSMEs) consumers. Research was conducted using a survey method, and the obtained data was subjected to a quantitative descriptive analysis using multiple linear regression. Based on the result of the research analysis, the number R2 (R Square) is 0.224 or (22.40%). This showed that the percentage contribution of the influence of the marketing mix of rendang as independent variables (product, price, place, promotion, and services) to the dependent variable (purchasing decision) is 22.40%. At the same time, the remaining 77.60% is influenced or explained by other variables that are not included in this research model. A significant simultaneous effect of five marketing mixes, i.e., product, price, place, promotion, and service, on consumers' purchasing decision of rendang was noticed. Price, place, and service positively affected the partial evaluation; however, product and promotion were not. To sum up, innovation on price, place, and service can be the primary consideration for the MSME to keep competitive in the rendang market.